2022
DOI: 10.3389/fsurg.2022.801708
|View full text |Cite
|
Sign up to set email alerts
|

Blood Urea Nitrogen-to-Albumin Ratio in Predicting Long-Term Mortality in Patients Following Coronary Artery Bypass Grafting: An Analysis of the MIMIC-III Database

Abstract: BackgroundThis study examined the role of blood urea nitrogen-to-albumin ratio (BAR) in predicting long-term mortality in patients undergoing coronary artery bypass grafting (CABG).MethodsIn this retrospective cohort study, patients undergoing CABG were enrolled from the Medical Information Mart for Intensive Care III (MIMIC III) database. Patients were divided into the three groups according to the optimal cutoff values of BAR determined by X-tile software. The survival curve was constructed by the Kaplan–Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Recently, Zhao D et al used Medical Information Mart for Intensive Care (MIMIC) III databases to analyze 1,462 patients receiving CABG, and found that BAR higher than 6.45 was associated with increased long-term mortality, which was consistent with our findings [ 14 ]. In their study, Zhao D et al found a higher BAR was an independent risk factor of one-year mortality (HR 3.904; 95% CI 2.559–5.956) [ 14 ]. In the present study, we excluded patients who died during admission and focused on the 8,073 patients discharged from surgical ICUs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Recently, Zhao D et al used Medical Information Mart for Intensive Care (MIMIC) III databases to analyze 1,462 patients receiving CABG, and found that BAR higher than 6.45 was associated with increased long-term mortality, which was consistent with our findings [ 14 ]. In their study, Zhao D et al found a higher BAR was an independent risk factor of one-year mortality (HR 3.904; 95% CI 2.559–5.956) [ 14 ]. In the present study, we excluded patients who died during admission and focused on the 8,073 patients discharged from surgical ICUs.…”
Section: Discussionsupporting
confidence: 89%
“…We used BAR 6.0 as the cut-point value in this study to achieve the balance between patients with high and low BAR. A number of BAR relevant studies have used distinct cut-point values [ 12 14 , 28 , 33 ], and we hence tested the consistence of our results using distinct cut-point values of BAR. We found a consistent association between week-one BAR and one-year post-hospital mortality among the enrolled critically ill surgical patients (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malondialdehyde (MDA), a reactive aldehyde and a final product of lipid peroxidation showed lower activity in the patients in in references to the controls Washeel et al, 2019), confirming studies (Gustaw-Rothenberg et al, 2010;Mohammed et al, 2021;Aysel et al, 2020). The Aβ to sialic acid binding on gangliosides in neuronal membranes promotes amyloidosis and induces cytotoxicity in AD (Rao et al, 2021;Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%